2016
DOI: 10.1097/aog.0000000000001258
|View full text |Cite
|
Sign up to set email alerts
|

Placental Alpha-Microglobulin-1 Test in Resource-Limited Settings

Abstract: Among women presenting at resource-limited settings with a history suspicious of preterm premature rupture of membranes between 24 and 36 weeks of gestation, our analysis provides evidence suggesting that PAMG-1 is the most cost-effective testing strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Perhaps due to exchange rate and tax issues, the price of these tests is very expensive in Brazil, a country where the Unified Health System pays hospitals approximately 395 reais (US $ 105) for a cesarean delivery. Despite the study by Echebiri et al , who reported a favorable cost–benefit ratio for the use of PAMG‐1 when resources are limited, we believe that the use of immunochromatographic tests should be restricted to inconclusive cases with the presence of bleeding. However, we agree that studies specifically designed for this purpose, with a thorough economic assessment, should be performed in Brazil and in other developing countries to confirm this conclusion.…”
Section: Discussionmentioning
confidence: 70%
“…Perhaps due to exchange rate and tax issues, the price of these tests is very expensive in Brazil, a country where the Unified Health System pays hospitals approximately 395 reais (US $ 105) for a cesarean delivery. Despite the study by Echebiri et al , who reported a favorable cost–benefit ratio for the use of PAMG‐1 when resources are limited, we believe that the use of immunochromatographic tests should be restricted to inconclusive cases with the presence of bleeding. However, we agree that studies specifically designed for this purpose, with a thorough economic assessment, should be performed in Brazil and in other developing countries to confirm this conclusion.…”
Section: Discussionmentioning
confidence: 70%
“…Fetal fibronectin is considered a biochemical marker of membrane/decidual activation, as is the increased expression of insulin growth factor binding protein (IGFBP)-1 [39][40][41][42][43][44][45][46][47][48][49][50][51][52] or α−1 microglobulin (also measurable with a PMG test in cervical and vaginal fluid) [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Membrane/decidual activation can be induced by the physiologic events that lead to spontaneous labor and delivery, or by pathologic insults, such as infection or inflammation [1,2,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Está asociado con una sensibilidad del orden del 5-30% y especificidad en el orden 5-12,9% de los pacientes. También es sabido de su fácil contaminación por otros factores como semen, orina, sangre y soluciones antisépticas (5).…”
Section: Introduccionunclassified